Effects of Blanching Pretreatment on the Quality Attributes of Freeze-Dried Red Dragon Fruit (Hylocereus costaricensis) - Nur Fitri Ramadhani; Junaedi Muhidong; Mursalim Mursalim; Abdul Waris; Febriana Intan Permata Hati (Program Studi Teknik Pertanian Universitas Hasanuddin, 2025)
Freeze drying is an effective method for preserving heat-sensitive fruits such as dragon fruit (Hylocereus costaricensis) by removing moisture through sublimation. This study aimed to evaluate the effect of blanching pretreatment on the quality attributes of freeze-dried dragon fruit, including moisture content, color, total soluble solids (TSS), and texture. A completely randomized design with two treatments (blanched at 90°C for 3 minutes and unblanched) and three replications was employed. Samples were cut into 1 mm and 3 mm thicknesses and freeze-dried at –50°C and 20 Pa for 24 hours. Results showed that blanching significantly reduced moisture content (final difference ≈1%), but also led to greater color degradation (lower L∗ and a∗ values, higher ΔE) and softer texture compared to unblanched samples. TSS values were lower in blanched samples. In conclusion, blanching enhances drying efficiency but compromises color, texture, and soluble solids retention in freeze-dried dragon fruit.